A Review on Visual Water Quality Monitoring System in Precision Aquaculture - Alter Jimat Embung; Ag Asri Ag Ibrahim; Muzaffar Hamzah; Mohammad Fadhli Asli (Trans Tech Publications, Switzerland, 2019)
This paper presents the review of available visual water quality monitoring and proposes a conceptual sonification model of audiovisual analytics for precision aquaculture. This study reviews the current practice of the visual water quality monitoring system used to interpret the complex fish farming data. This study also explores the possibility of using an auditory display, by using sound as complementary elements to communicate information from the system to the user.